2015
DOI: 10.1007/5584_2015_134
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation in Advanced Lung Cancer Patients During Chemotherapy

Abstract: The aim of this study was to investigate the utility of pulmonary rehabilitation for improving of exercises efficiency, dyspnea, and quality of life of patients with lung cancer during chemotherapy. After the enrollment selection, the study included 20 patients with newly diagnosed advanced lung cancer and performance status 0-2. There were 12 patients randomly allocated to the pulmonary rehabilitation group and another 8 constituted the control group that did not undergo physical rehabilitation. Both groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 14 publications
0
43
2
2
Order By: Relevance
“…Recently, several trials have reported positive results with supervised PA interventions. 23 - 25 To be sure, supervised PA interventions are able to implement more intense PA in a safe setting. However, the frequency of PA sessions is limited, travel burden is placed on the patient, and increases in activity outside the activity sessions are not assured.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several trials have reported positive results with supervised PA interventions. 23 - 25 To be sure, supervised PA interventions are able to implement more intense PA in a safe setting. However, the frequency of PA sessions is limited, travel burden is placed on the patient, and increases in activity outside the activity sessions are not assured.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies have addressed PA in patients with advanced-stage lung cancer. These studies have shown that increasing PA is feasible 33 and improves mobility, fatigue, sleep, pain, strength, dyspnea, anxiety, depression, and QoL, 27 , 28 , 34 , 35 though adherence may be <50%. 33 Because most patients with lung disease can perform some type of exercise with variable compliance, the potential for digital accelerometers to remotely monitor low-impact PA is appealing.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 11 studies, including six RSs and five non-randomized studies (NRSs), that consisted of 922 participants were included in our systematic review. [15][16][17][18][19][20][21][22][23][24][25] We classified the selected studies as either an "intervention-control" or "before-after" study. For the intervention-control study, four of the six RSs were included.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For the intervention-control study, four of the six RSs were included. [15][16][17][18] The other two RSs compared the exercise groups (cardiovascular vs. resistance and aerobic vs. resistance).…”
Section: Study Characteristicsmentioning
confidence: 99%